Originally Posted by

**Detanon** Solve the simultaneous equations

$\displaystyle 2x + y - z = 3

3x + 2y + 2z = 13

x - 3y+ z = -6 $

and deduce the soltuions of the simultaneous equations.

$\displaystyle 2/(a+3) + 1/(b-2) - 1/(1-c) = 3 $

$\displaystyle 3/(a+3) + 2/(b-2) + 2/(1 - c) = 13$

$\displaystyle 1/(a+3) - 3/(b-2) + 1/(1-c) = -6 $

(sorry i dont know how to do fractions.)

I've solved the simultaneous equations. x = 1, y =3, z =2

but for the second part I dont know what to do. Can anyone help me please?

Thanks.